If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3xm + -3x * 4 = -2m + -8 Reorder the terms for easier multiplication: 2x + -3mx + -3 * 4x = -2m + -8 Multiply -3 * 4 2x + -3mx + -12x = -2m + -8 Reorder the terms: -3mx + 2x + -12x = -2m + -8 Combine like terms: 2x + -12x = -10x -3mx + -10x = -2m + -8 Reorder the terms: -3mx + -10x = -8 + -2m Solving -3mx + -10x = -8 + -2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2m' to each side of the equation. -3mx + 2m + -10x = -8 + -2m + 2m Reorder the terms: 2m + -3mx + -10x = -8 + -2m + 2m Combine like terms: -2m + 2m = 0 2m + -3mx + -10x = -8 + 0 2m + -3mx + -10x = -8 Add '10x' to each side of the equation. 2m + -3mx + -10x + 10x = -8 + 10x Combine like terms: -10x + 10x = 0 2m + -3mx + 0 = -8 + 10x 2m + -3mx = -8 + 10x Reorder the terms: 8 + 2m + -3mx + -10x = -8 + 10x + 8 + -10x Reorder the terms: 8 + 2m + -3mx + -10x = -8 + 8 + 10x + -10x Combine like terms: -8 + 8 = 0 8 + 2m + -3mx + -10x = 0 + 10x + -10x 8 + 2m + -3mx + -10x = 10x + -10x Combine like terms: 10x + -10x = 0 8 + 2m + -3mx + -10x = 0 The solution to this equation could not be determined.
| 4x-5x-3=0 | | 2x+8y=x-2y | | Y=-5/3-5 | | 2x--2=2 | | 3.4=15.9-5w | | 5x^2+3x=2x(x+6) | | 6p+6=5p+14 | | z+0.9=3.1 | | x(2-12-3m)=-8-2m | | r(1.4+35)=436.60 | | 4x-7=59-7x | | x-1/4=5 | | 2xc+-1c^2x+x=-10+5c | | 4x-3-4=24 | | x+2cx-c^2x=-10+5c | | X^2-25-144=0 | | (6*6-3*3*3)/7 | | (u^4/-2w^2)^2 | | -56=y-49 | | -67=-32n+29 | | 20(b+7)=-20 | | 5b-16=39 | | 76=y/4 | | 2.1x+1.3=-9.2 | | 8.5x-6.5=6.8x+10.0 | | 6(v+3)-2v=2(2v+1)-11 | | 12x-3(3x-6)=2x+2 | | 25=13+8d | | 240=170+5d | | 10f+5= | | -3(l+4)-l-3=-4(l+5)+5 | | 0.8x-0.4(60+x)=0.067(60) |